2022
DOI: 10.1186/s12903-022-02134-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of caries diagnostic thresholds of DMFT, ICDAS II and CAST in the estimation of caries prevalence rate in first permanent molars in early permanent dentition—a cross-sectional study

Abstract: Background The actual burden of dental caries prevalence varies with the caries assessment tool used. Therefore, the present study evaluated the caries diagnostic potentials of Decayed, Missing and Filled Teeth (DMFT); International Caries Detection and Assessment System (ICDAS) II and Caries Assessment Spectrum and Treatment (CAST) indices in estimating the caries prevalence rate of first permanent molar (FPM) in Saudi male children aged 7–9 years. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
2
10
1
1
Order By: Relevance
“…The current study showed a highly significant difference ( p < 0.001) in caries prevalence between WHO and ICDAS II. This finding is supported by many other studies 2,3,5,17,19–21 . The discrepancy between the two systems might be due to the failure of the WHO system to include noncavitated lesions.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The current study showed a highly significant difference ( p < 0.001) in caries prevalence between WHO and ICDAS II. This finding is supported by many other studies 2,3,5,17,19–21 . The discrepancy between the two systems might be due to the failure of the WHO system to include noncavitated lesions.…”
Section: Discussionsupporting
confidence: 75%
“…A tooth that had been crowned because of previous decay was also recorded studies. 2,3,5,17,[19][20][21] The discrepancy between the two systems might be due to the failure of the WHO system to include noncavitated lesions.…”
Section: Missing Toothmentioning
confidence: 99%
“…Given the growing interest in minimally invasive dentistry, detecting precavitated lesions seems to be considered. Nonetheless, adopting such an approach might not be viable for epidemiological surveys, especially in low‐income settings where resources are scarce 51 . Besides, most studies included in this meta‐analysis reported data from children aged 5 years and older; of those, all but one reported data on both primary and permanent tooth caries.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, adopting such an approach might not be viable for epidemiological surveys, especially in low-income settings where resources are scarce. 51 Besides, most studies included in this metaanalysis reported data from children aged 5 years and older; of those, all but one reported data on both primary and permanent tooth caries. This allowed us consider the nonage-dependent approach and further avoided the common caries-free pattern seen in permanent teeth of individuals in their early mixed dentition.…”
Section: Discussionmentioning
confidence: 99%
“…For cavitated carious lesions, both indices tend to report similar prevalence rates. Nevertheless, dmft index is unable to detect non-cavitated lesions cases, unlike the ICDAS which has the advantage of distinguishing between the stages of caries progression in early enamel, enamel, and dentin [91,92]. Hence the variation between the two indices needs to be taken into consideration while interpreting the results of this review.…”
Section: Discussionmentioning
confidence: 99%